Population pharmacokinetics and exposure-response analyses of varenicline in adolescent smokers - Daryl J. Fediuk; Kevin Sweeney; Vaishali Sahasrabudhe; Thomas McRae; Wonkyung Byon (Wiley, 2021)
Abstract Varenicline is an approved smoking cessation aid in adults. Population pharmacokinetics (popPK) and exposure-response (ER) (continuous abstinence rates [CAR] weeks 9‒12 and nausea/vomiting incidence) for varenicline in adolescent smokers were characterized using data from two phase 1 and one phase 4 studies. A one‐compartment popPK model with first‐order absorption and elimination adequately fitted the observed data. The effect of female sex on apparent clearance was significant. Apparent volume of distribution increased with body weight and decreased by 24%, 15%, and 14% for black race, "other" race, and female sex, respectively. The observed range of exposure in the phase 4 study was consistent with that expected for each dose and body‐weight group from the results obtained in adolescent PK studies, supporting that varenicline dose and administration were appropriate in the study. The relationship between CAR9‒12 and varenicline area under the concentration-time curve (AUC) from 0 to 24 hours (AUC24) was nonsignificant (p = 0.303). Nausea/vomiting incidence increased with AUC24 (p < 0.001) and was higher in females. Varenicline PK and ER for tolerability in adolescent smokers were comparable with adults, while ER for efficacy confirmed the negative results reported in the phase 4 study.